BANDPASS FILTER MICROSTRIP FREKUENSI 6 GHZ MENGGUNAKAN SPLIT RING RESONATOR BERBASIS DEFECTED GROUND STRUCTURE UNTUK RADAR C-BAND - Awaludin, Ajrul Faza; Hidayat, M. Reza; Alimudin, Erna (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2023)
In telecommunications, filters are devices that play an important role in a telecommunications system. One of them is a bandpass filter that can pass signals with a passband frequency and cut off the stopband frequency. In the process, various kinds of signal interference will be found that can interfere with the quality of electromagnetic waves. This research will design and realize a microstrip bandpass filter that can pass the 6 GHz frequency with a minimum bandwidth of ? 100 MHz for C-Band Radar applications. This filter is designed using a square open loop resonator which will be simulated using the CST studio suite 2019 which will be realized using a 4-epoxy FR substrate. In this study the design of a microstrip bandpass filter was carried out with three stages of design simulation to determine the characteristics of the square open loop resonator, split ring resonator, and defected ground structure design. Based on the results of the final design of the microstrip bandpass filter design, the simulation results obtained work at a resonant frequency of 6 GHz with a return loss value of -32.098 dB, an insertion loss value of -0.40148 dB and a bandwidth of 97.3 MHz. The results of bandpass filter fabrication measurements were obtained at a resonant frequency of 6 GHz, the results obtained were in accordance with the required specifications with a return loss of -29.09 dB, an insertion loss of -2.75 dB with a bandwidth of 485.4 MHz.